The study of protein recruitment to laser-induced DNA lesions can be distorted by photoconversion of the DNA binding dye Hoechst [version 2; peer review: 1 approved, 2 approved with reservations] - Verena Hurst; Susan M. Gasser (F1000Research, 2019)
A commonly used approach for assessing DNA repair factor recruitment in mammalian cells is to induce DNA damage with a laser in the UV or near UV range and follow the local increase of GFP-tagged proteins at the site of damage. Often these measurements are performed in the presence of the blue DNA dye Hoechst, which is used as a photosensitizer. However, a light-induced switch of Hoechst from a blue-light to a green-light emitter will give a false positive signal at the site of damage.  Thus, photoconversion signals must be subtracted from the overall green-light emission to determine true recruitment. Here we demonstrate the photoconversion effect and suggest control experiments to exclude false-positive results.